MODERNISASI PEMBELAJARAN: IMPLEMENTASI PRINSIP-PRINSIP ANDRAGOGI QUR’ĀNI DALAM TRAINING THE ESQ WAY 165 - Sofiuddin Sofiuddin (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2017)
The thesis proves that as more Qur'anic Andragogy principles are applied as could build humanistic-rational individual and religious adult learner. This research does not agree with: 1) theory of Andragogy Malcolm Shepherd Knowles (1950), which emphasizes learning centered on learners and educators as facilitators. 2). Gülden Akin and Serap Karabacak Aşir (2013) statesو that Andragogy can be applied to any age level. In addition, this study also supports; 1). Trumper, which confirms that the educator other than as facilitator should also play a role in providing the experience and finding innovative ways to help learners, 2). Nadiyah Jamaluddin (1983), confirms that no doubt the education of children and adults is different, because they are different characters, the tools they need and purpose in learning. 3). Yvonne Hunter (2011) stated very important to notice that learning can become more self-directed learning, so that the learning-process result can be perceived. Based on the fact that the lack of literature on Qur'anic Andragogy causes less familiar and less developed in the community. Whereas the concept is a very big thought to contribute on the development adult education which directs learners to independence, creative, preparedness to learn and achieve the orientation of learning. In addition, the existence of the principles of Qur'anic andragogy is only a formula that has not been studied from the concept of implementation to education models like formal, informal or nonformal education. Thus, the presence of this study can be a representation and the foundation of the Islamic view. The primary data sources in this study include and Ary Ginanjar's creation like “ESQ: Rahasia Sukses Membangun Kecerdasan Emosi & Spiritual”, trainings, the results of the interview, observation and dissertation entitled “Konsep Andragogi Dalam Al-Qur’an”. While secondary data sources include some literature that related to theory Andragogy, Knowles' creation, a variety of thoughts which related to adult education, either in the form of books, dissertations, scientific journals and other relevant data sources. This research implementation of Qur'anic Andragogy principles is enriched with several disciplines such as; scientific, artistic, clinical psychology, social psychology, adult education and humanism.